DirectRMDB: a database of post-transcriptional RNA modifications unveiled from direct RNA sequencing technology. Issue Volume 51:Issue D1(2023) (16th November 2022) - Zhang, Yuxin; Jiang, Jie; Ma, Jiongming; Wei, Zhen; Wang, Yue; Song, Bowen; Meng, Jia; Jia, Guifang; de Magalhães, João Pedro; Rigden, Daniel J; Hang, Daiyun; Chen, Kunqi
Abstract: With advanced technologies to map RNA modifications, our understanding of them has been revolutionized, and they are seen to be far more widespread and important than previously thought. Current next-generation sequencing (NGS)-based modification profiling methods are blind to RNA modifications and thus require selective chemical treatment or antibody immunoprecipitation methods for particular modification types. They also face the problem of short read length, isoform ambiguities, biases and artifacts. Direct RNA sequencing (DRS) technologies, commercialized by Oxford Nanopore Technologies (ONT), enable the direct interrogation of any given modification present in individual transcripts and promise to address the limitations of previous NGS-based methods. Here, we present the first ONT-based database of quantitative RNA modification profiles, DirectRMDB, which includes 16 types of modification and a total of 904, 712 modification sites in 25 species identified from 39 independent studies. In addition to standard functions adopted by existing databases, such as gene annotations and post-transcriptional association analysis, we provide a fresh view of RNA modifications, which enables exploration of the epitranscriptome in an isoform-specific manner. The DirectRMDB database is freely available at: http://www.rnamd.org/directRMDB/ .